2021
DOI: 10.1097/md.0000000000024456
|View full text |Cite
|
Sign up to set email alerts
|

Severe laryngeal edema caused by Pseudoterranova species

Abstract: Rationale: Severe laryngeal edema can cause upper airway obstruction, which is fatal. Pseudoterranova , an uncommon nematode of the family Anisakidae, predominantly invades the stomach after ingestion of the nematodes in raw or undercooked marine fish. There have been a few reports of development of severe laryngeal edema caused by the nematode invading the base of the tongue. Patient concerns: A 69-year-old Japanese woman complained of stuffy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The third-stage juvenile emerging from the egg is swallowed by benthic crustaceans and, moving along trophic chains, accumulates in fish [4,5]. Third-stage juveniles of these nematodes cause an important fish-borne zoonosis (e.g., [6][7][8][9][10][11][12][13]).…”
Section: Introductionmentioning
confidence: 99%
“…The third-stage juvenile emerging from the egg is swallowed by benthic crustaceans and, moving along trophic chains, accumulates in fish [4,5]. Third-stage juveniles of these nematodes cause an important fish-borne zoonosis (e.g., [6][7][8][9][10][11][12][13]).…”
Section: Introductionmentioning
confidence: 99%
“…infections (Buchmann & Mehrdana, 2016; Rahmati et al., 2020; Shamsi & Sheorey, 2018). Medical case studies of Pseudoterranova infections show their pathogenic potential and relevance (Arcos et al., 2014; Arizono et al., 2011; Brunet et al., 2017; Cavallero et al., 2016; Llorens et al., 2018; Menghi et al., 2020; Mercado et al., 1997, 2001; Mitsuboshi et al., 2017; Murata et al., 2018; Nordholm et al., 2020; Pinel et al., 1996; Ramanan et al., 2013; Sánchez‐Alonso et al., 2020; Suzuki et al., 2021; Timi et al., 2014; Torres et al., 2007; Weitzel et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Food allergies are reported to affect approximately 5% of infants and 3–4% of adults in Western countries [ 3 ]. The symptoms of food allergy vary from mild itching, diarrhea, and cough to severe life-threatening throat edema and anaphylactic shock [ 4 ]. Food allergies can cause chronic inflammation [ 5 , 6 , 7 ], and many studies have shown that inflammation can be linked to the pathogenesis of diabetes [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…mTOR in the intestine may link energy supply with the production of GLP-1 in L cells [ 38 ]. The proposed mechanism of action of GLP-1 is believed to occur through activation of the PI3K/AKT signaling pathway and downstream of the mechanistic target of rapamycin (mTOR) kinase [ 4 , 5 , 8 ]. GLP-1 protects insulin-secreting cells against apoptosis and restrains high glucose-induced apoptosis by impeding oxidative stress through PI3K-dependent signaling pathways [ 1 , 9 ].…”
Section: Introductionmentioning
confidence: 99%